Polarized distribution of extracellular nucleotides promotes gravity-directed polarization of development in spores of Ceratopteris richardii - Cannon, Ashley E.; Vanegas, Diana C.; Sabharwal, Tanya; Salmi, Mari L.; Wang, Jeffrey; Clark, Greg; McLamore, Eric S.; Roux, Stanley J. (Frontiers in Plant Science, 2023)
Gravity directs the polarization of Ceratopteris fern spores. This process begins with the uptake of calcium through channels at the bottom of the spore, a step necessary for the gravity response. Data showing that extracellular ATP (eATP) regulates calcium channels led to the hypothesis that extracellular nucleotides could play a role in the gravity-directed polarization of Ceratopteris spores. In animal and plant cells ATP can be released from mechanosensitive channels. This report tests the hypothesis that the polarized release of ATP from spores could be activated by gravity, preferentially along the bottom of the spore, leading to an asymmetrical accumulation of eATP. In order to carry out this test, an ATP biosensor was used to measure the [eATP] at the bottom and top of germinating spores during gravity-directed polarization. The [eATP] along the bottom of the spore averaged 7-fold higher than the concentration at the top. All treatments that disrupted eATP signaling resulted in a statistically significant decrease in the gravity response. In order to investigate the source of ATP release, spores were treated with Brefeldin A (BFA) and gadolinium trichloride (GdCl3). These treatments resulted in a significant decrease in gravity-directed polarization. An ATP biosensor was also used to measure ATP release after treatment with both BFA and GdCl3. Both of these treatments caused a significant decrease in [ATP] measured around spores. These results support the hypothesis that ATP could be released from mechanosensitive channels and secretory vesicles during the gravity-directed polarization of Ceratopteris spores.